Strategies and resources used by public health units to encourage COVID-19 vaccination among priority groups: a behavioural science-informed review of three urban centres in Canada - Tori Langmuir; Mackenzie Wilson; Nicola McCleary; Andrea M. Patey; Karim Mekki; Hanan Ghazal; Elizabeth Estey Noad; Judy Buchan; Vinita Dubey; Jana Galley; Emily Gibson; Guillaume Fontaine; et al. (BMC Public Health)
Abstract Background Ensuring widespread COVID-19 vaccine uptake is a public health priority in Canada and globally, particularly within communities that exhibit lower uptake rates and are at a higher risk of infection. Public health units (PHUs) have leveraged many resources to promote the uptake of recommended COVID-19 vaccine doses. Understanding barriers and facilitators to vaccine uptake, and which strategies/resources have been used to address them to date, may help identify areas where further support could be provided. We sought to identify the strategies/resources used by PHUs to promote the uptake of the first and third doses of the COVID-19 vaccine among priority groups in their jurisdictions. We examined the alignment of these existing strategies/resources with behavioral science principles, to inform potential complementary strategies/resources. Methods We reviewed the online and in-person strategies/resources used by three PHUs in Ontario, Canada to promote COVID-19 vaccine uptake among priority groups (Black and Eastern European populations, and/or neighbourhoods with low vaccine uptake or socioeconomic status). Strategies/resources were identified from PHU websites, social media, and PHU liaison. We used the Behaviour Change Techniques (BCT) Taxonomy – which describes 93 different ways of supporting behaviour change – to categorise the types of strategies/resources used, and the Theoretical Domains Framework – which synthesises 14 factors that can be barriers or facilitators to decisions and actions – to categorise the barriers and facilitators addressed by strategies/resources. Results PHUs operationalised 21 out of 93 BCTs, ranging from 15 to 20 BCTs per PHU. The most frequently operationalised BCTs were found in strategies/resources that provided information about COVID-19 infection and vaccines, increased access to COVID-19 vaccination, and integrated social supports such as community ambassadors and engagement sessions with healthcare professionals. Identified BCTs aligned most frequently with addressing barriers and facilitators related to Knowledge, Environmental context and resources, and Beliefs about consequences domains. Conclusion PHUs have used several BCTs to address different barriers and facilitators to COVID-19 vaccine uptake for priority groups. Opportunities should be pursued to broaden the scope of BCTs used (e.g., operationalizing the pros and cons BCT) and barriers/facilitators addressed in strategies/resources for ongoing and future COVID-19 vaccine uptake efforts among general and prioritised populations.